On the issue of psychodiagnosis of Internet addiction against the background of social isolation and security crisis - A. M. Stoliarenko; A. D. Horodokin (Сучасні медичні технології)
Aim: to analyze the diagnostic informativeness of the Kimberly Young’s Internet Addiction Test in the conditions of social isolation and security crisis in Ukraine.